Avalia????o e progress??o continuada: educa????o na contram??o? - Camur??a, Yonara de Albuquerque (2016)
The Law of Directives and Bases of Education no. 9.394 (1996) instituted the restructuring of the educational system of basic education in Brazil, proposing an overhaul in school evaluation practice and suitability for the regime of cycles and continued progression in public schools, which replaced approval/disapproval system that valued the grade as learning indicator. This research addresses the evaluation with emphasis on the regime of continued progression, suggested in legislation and implemented in S??o Paulo since 1998. The objectives of this work are: to understand the vision of teachers in relation to the evaluative practice proposed in the continued progression system; relate teaching practices to what is required by law; identify the changes brought about by the regime of continued progression for the pedagogical work in cycle II of elementary school. Bibliographical and field surveys were carried out; teachers of public schools working under the regime of continued progression were interviewed because they are considered important actors in the educational process in which they are directly involved. The research points as its theoretical base two axes: the complex thought of Edgar Morin, that understands the evaluative action as a dynamic and ongoing process, in which are considered fundamental aspects of human development; and evaluative conceptions of the authors Jussara Hoffmann, Cipriano Luckesi, Ana Maria Saul and Jos?? Eust??quio Rom??o. The interviews were analyzed according to the categories of complex thinking: the idea of reconnection; the dialogic, recursive and hologramatic principles; strategy and program; the ecology of action; and mutual and interrelated causality. Research demonstrated the strong presence of culture in the evaluation process, since the ways of thinking and acting, both for teachers and students are still rooted in the ancient evaluating practice, making it difficult for the regime of continued progression to perform the function that aims to improve the quality of education.